The Effectiveness of Micronutrient Supplementation in Improving Nutritional Status: A Literature Review - Nugroho, Muhammad Ismail; Handini, Laksmi Suci (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Micronutrient deficiencies, such as iron, vitamin A, zinc, and iodine, remain critical nutritional issues in developing countries, including Indonesia. These deficiencies significantly impact public health, particularly among children and pregnant women, causing conditions like anemia, stunting, and increased susceptibility to infections. Objective: This study aims to evaluate the effectiveness of micronutrient supplementation in improving nutritional status, with a focus on identifying challenges and proposing solutions for sustainable interventions. Methods: A systematic literature review was conducted using sources from Google Scholar. Keywords included “micronutrient supplementation,” “nutritional status improvement,” and “micronutrient deficiencies.” Journals were selected based on criteria such as publication within the last 20 years, relevance, and inclusion of clinical trials or human case studies. Data were classified by micronutrient type, target population, and measured outcomes. Results and Discussion: Micronutrient supplementation significantly improves nutritional status in vulnerable groups. Iron supplementation reduces anemia rates and associated complications, while vitamin A supplementation decreases infection-related morbidity and mortality. Zinc supplementation alleviates stunting and reduces diarrhea and respiratory infections in children. However, challenges such as limited accessibility, low compliance, and programmatic barriers persist, necessitating integrated approaches for sustainable outcomes. Conclusion: Micronutrient supplementation is effective in improving nutritional and health status, particularly among children and pregnant women. To optimize these outcomes, supplementation programs should be complemented by education, food-based interventions, and supportive government policies that ensure accessibility and sustainability.